SJPS 2022
DOI: 10.34135/sjps.220104
|View full text |Cite
|
Sign up to set email alerts
|

Political Messianism in Portugal, the Case of André Ventura

Abstract: The article aims to discuss Populist Radical Right (“PRR”) through the case of the Portuguese party, Chega (“enough”), presenting its leader, André Ventura, as a political Messiah. Confronting the literature, this article emphasises that, until Ventura came into the scene and contrary to the idea of Portuguese exceptionalism, populism was historically evident in Portuguese politics long before the advent of Chega. Although much has been written about the PRR party, this article presents its leader, André Ventu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In his study on political messianism, Dias demonstrated that the leader of Chega navigates the waters of Portuguese colonial memory with a narrative of a country devoid of racism and political messianism rooted in Sebastianism in the case of Portugal, representing a poetic-prophetic aspiration for the return of the political savior. To acquire a religious aura, Ventura employs elements of popular Portuguese religiosity, such as the Miracle of Fatima (Dias, 2022).…”
Section: Results' Discussionmentioning
confidence: 99%
“…In his study on political messianism, Dias demonstrated that the leader of Chega navigates the waters of Portuguese colonial memory with a narrative of a country devoid of racism and political messianism rooted in Sebastianism in the case of Portugal, representing a poetic-prophetic aspiration for the return of the political savior. To acquire a religious aura, Ventura employs elements of popular Portuguese religiosity, such as the Miracle of Fatima (Dias, 2022).…”
Section: Results' Discussionmentioning
confidence: 99%